Educational Needs of Mothers about using Oral Rehydration Salt (ORS) at Home During Acute Diarrhea in Children under 5 at Urmia Population Research Center - Rezapour, Baratali (Journal of Public Health International, 2020)
Preventable factors such as infectious diseases (pneumonia, diarrhea, and malaria), malnutrition and neonatal complications are still the leading cause of child mortality worldwide 1 In 2013, it is estimated that 6.3 million babies born worldwide died before the age of 5, and approximately 9.2% of these deaths were due to diarrheal diseases 23 in simple, accessible ways, and effective treatment can reduce diarrhea-related mortality and make hospital admissions unnecessary, and the role of mothers is the most important 4. Since the presentation of Oral Rehydration Therapy (ORT) in 1979, mortality has reduced. Diarrhea has had a steady downward trend 5. If mothers who have children under 5 years of age, used correctly ORS, they could easily resolve the problem of dehydration in acute diarrhea 6. Mothers didn’t use correctly ORS because of their Low literacy and lack of knowledge and wrong attitude about ORT7. Some health care workers provide mothers’ required equipments, regardless of their educational needs, and mothers may not use ORS. In this study, health workers identified mothers' educational needs and subsequently they trained them about using ORS at home in acute diarrhea in children under 5 years of age.
Keywords: Mothers; Educational needs; Diarrhea; ORS